Natural products and drug discovery: a survey of stakeholders in industry and academia - Amirkia, Vafa; Heinrich, Michael (Frontiers in Pharmacology, 2015)
Context: In recent decades, natural products have undisputedly played a leading role in the development of novel medicines. Yet, trends in the pharmaceutical industry at the level of research investments indicate that natural product research is neither prioritized nor perceived as fruitful in drug discovery programmes as compared with incremental structural modifications and large volume HTS screening of synthetics. Aim: We seek to understand this phenomenon through insights from highly experienced natural product experts in industry and academia. Method: We conducted a survey including a series of qualitative and quantitative questions related to current insights and prospective developments in natural product drug development. The survey was completed by a cross-section of 52 respondents in industry and academia. Results: One recurrent theme is the dissonance between the perceived high potential of NP as drug leads among individuals and the survey participants’ assessment of the overall industry and/or company level strategies and their success. The study’s industry and academic respondents did not perceive current discovery efforts as more effective as compared with previous decades, yet industry contacts perceived higher hit rates in HTS efforts as compared with academic respondents. Surprisingly, many industry contacts were highly critical to prevalent company and industry-wide drug discovery strategies indicating a high level of dissatisfaction within the industry. Conclusions: These findings support the notion that there is an increasing gap in perception between the effectiveness of well established, commercially widespread drug discovery strategies between those working in industry and academic experts. This research seeks to shed light on this gap and aid in furthering natural product discovery endeavors through an analysis of current bottlenecks in industry drug discovery programmes.